Crisis Management of Enterprises and Post-War Reconstruction in Ukraine - Балджи, Марина Дмитрівна; Baldzhy, Maryna D.; Yurii, Shulzhyk; Lesia, Moroz-Rekotova; Lidiya, Lisovska (My University, 2023)
It has been proven that the anti-crisis management program can determine the presence of three enterprise development systems that determine the choice of directions for anti-crisis management: “conditionally stable system,” in which passive anti-crisis management is sufficient, “system with the manifestation of crisis phenomena,” and “general crisis system,” which requires the application of active anti-crisis measures. The goals of enterprise anti-crisis management vary depending on the type of financial system of the enterprise. Thus, anti-crisis management under the conditionally stable system aims to diagnose the indicators of enterprise activity for timely detection of manifestations of crisis phenomena. In the system expressing crisis phenomena, anti-crisis management aims to localize detected crises, overcome their negative impact, and restore pre-crisis indicators. The goal of anti-crisis management under the general crisis system is to manage the enterprise in conditions of prolonged crisis (stagnation). Each model of anti-crisis management has corresponding stages, the implementation of which is aimed at minimizing the negative impact of crisis phenomena on the enterprise’s activity. The methods of anti-crisis management during the war have been systematized. The methods of anti-crisis management can be attributed to the entire set of methodological tools that include a complex of measures from pre-crisis diagnosis to methods of its elimination and overcoming. Based on the essential characteristics and the need to decide on applying anti-crisis methods at each stage of the enterprise’s life cycle, their consideration from the perspective of diagnostic and crisis management methods is envisaged. Based on the application of a methodological approach to the formation of the system of forecasting anti-crisis management measures at the enterprise, the use of an algorithm for anti-crisis management to choose the direction of anti-crisis management at enterprises (passive or active) has been proposed.
Crisis Management of Enterprises and Post-War Reconstruction in Ukraine / Y. Shulzhyk, L. Moroz-Rekotova, V. Kiptenko, L. Lisovska, M. Baldzhy // Economic Affairs. – 2023. – Vol. 68, № 3. – Р. 1693-1699. DOI: 10.46852/0424-2513.3.2023.34
Keywords: Crisis management; war; reconstruction; market economy; business management; Research Subject Categories::SOCIAL SCIENCES